Visualising spaces of global inaccessibility - Hennig, B (Springer Netherlands, 2016)
Wilderness is normally visualised using conventional mapping approaches showing the least touched spaces on the planet. Because most of the world’s population lives in very limited spaces, this is a useful method of representation. The effects of human action, however, go much further than that, resulting in much of the land area being relatively close to humankind while the remotest and ‘wildest’ spaces are very little areas on a normal map. This chapter looks at alternative ways to visualise the most remote parts of the land area: by deploying a so-called gridded cartogram transformation to data about the (in)accessibility of a place, the resulting cartograms reveal the areas and the extent of the remotest spaces in a much less common way. Gridded cartograms are created by using an equally distributed grid onto which a density-equalising cartogram technique is applied. Each individual grid cell is resized according to its the average travel time to the nearest larger city. This technique is not only applied to the global scale, but also to regional and national-level data. The results are maps that give the remotest places most space and provide a unique and highly visual perspective on the spatial dimension of remoteness.